2018
DOI: 10.1002/pon.4734
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional, psycho‐social intervention to facilitate resilience and reduce supportive care needs for patients with cancer: Results of a noncomparative, randomized phase II trial

Abstract: Neither LI-IPSC-C nor HI-IPSC-C interventions reached the desired threshold. HI-IPSC-C showed positive effects on secondary outcomes and was feasible. Resilience as measured by the CD-RISC may not be the optimal outcome measure for this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“… 37 Therefore, within a complex intervention for supportive care in cancer the researchers tried to facilitate resilience and reduce unmet supportive care needs. 38 Resilience levels could only be significantly influenced in a few participants. It must be concluded that it remains unclear whether resilience can be trained in patients with MM and other cancer entities.…”
Section: Discussionmentioning
confidence: 96%
“… 37 Therefore, within a complex intervention for supportive care in cancer the researchers tried to facilitate resilience and reduce unmet supportive care needs. 38 Resilience levels could only be significantly influenced in a few participants. It must be concluded that it remains unclear whether resilience can be trained in patients with MM and other cancer entities.…”
Section: Discussionmentioning
confidence: 96%
“…The first two coupled SACT-PI steps ‘Assess patient and family’ and ‘Educate and inform patient’ can be implemented independent of the cultural or ethnical context 97 ; the steps include assessing patient preference for information and involvement in decision making. Clinicians other than physicians—namely oncology nurses 96 —can carry out these two steps, or physicians working in a culture and clinical pathways of integrated oncology and cancer PC can be involved. 98 …”
Section: Discussionmentioning
confidence: 99%
“…One systematic review of 25 randomised trials of resilience interventions found favourable effects for enhancing resilience, improving stress and reducing depressive symptoms among a wide range of populations including soldiers, employees, students and physicians. 20 Among cancer survivors, a handful of resilience-based interventions have shown promising results for outcomes such as resilience, stress and anxiety [21][22][23][24] and a few observational studies have shown an association between resilience among caregivers of adult patients with cancer and caregiver outcomes such as self-reported health status, anxiety and depression. 3 25 26 However, no study has yet been carried out for a resilience-based intervention for cancer caregivers.…”
Section: Resilience As a Therapeutic Approachmentioning
confidence: 99%